Emotional Gaze: The Effects of Gaze Direction on the Perception of Facial Emotions - Liang, Jing; Zou, Yu-Qing; Liang, Si-Yi; Wu, Yu-Wei; Yan, Wen-Jing (Frontiers in Psychology, 2021)
Previous research found that a direct gaze shares an approach-orientated signal with the emotions of anger and joy, whereas an averted gaze shares an avoidance-orientated signal with fear and sadness. In this research, we attempted to verify the Shared Signal Theory by using different materials on Asian participants. In Exp. 1, we used photos of models exhibiting direct and averted gazes in order to study the effects of gaze direction on the perception of emotion. The results show that the direct gaze, relative to the averted gaze, increased the likelihood of a subject perceiving a happy mood; the averted gaze increased the likelihood that anger and fear would be perceived. To further investigate whether such a pattern exists on a smile face, in Exp. 2 we used the smiling faces with either direct or averted eye gaze. Results is like those in Exp. 1. The effect of gaze direction was verified, but the pattern expressed is different. The difference between our work and previous studies may be due to the materials employed, which were more ecological, as well as the participants, who were from a different culture. This study suggested that different cultures may lead to different patterns of Shared Signals between approach-avoidance and emotions.